Earthquake, dolphins and big data - the challenges in Hydrographic Surveying - Caie, S.; Wallen (New Zealand)., B. (The International Hydrographic Review, 2018)
In 2016, Land Information New Zealand (LINZ) completed an evidence-based, risk-led assessment (LINZ, 2016a) of the accuracy and adequacy of nautical charting in New Zealand. The results identified Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au as areas of heightened risk. LINZ, in partnership with Marlborough District Council (MDC), developed a programme of work to carry out hydrographic surveys for safety-of-navigation and scientific purposes. This collaboration was a first for both organisations. The survey requirements called for a variety of deliverables, in a number of areas, on a variety of dates. Given the size of the survey area (440km2), the number of water users, time constraints, inquisitive dolphins and large volumes of data, the project posed some known challenges. Throw in an earthquake and the challenges increase. Managed overall by LINZ, the prime contractor was the National Institute of Water and Atmospheric Research (NIWA), who will deliver all the science components. Discovery Marine Limited (DML) was sub-contracted to provide the hydrographic survey compo-nents, which included the provision of the Surveyor-In-Charge and the delivery of safety-of-navigation components. After wading through the vast dataset, final survey deliverables have now been received and accepted by LINZ. The data will be used to update the charts. This article describes the rationale behind the survey and discusses the challenges encountered during the project.